Sensitivity and packaging improvement of an LCP pressure sensor for intracranial pressure measurement via FEM simulation - Preedipat Sattayasoonthorn; Jackrit Suthakorn; Sorayouth Chamnanvej (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A biocompatible liquid crystal polymer (LCP) pressure sensor is proposed for measuring intracranial pressure (ICP) in Traumatic Brain Injury (TBI) patients. Finite element method using COMSOL multiphysics is employed to study the mechanical behavior of the packaged LCP pressure sensor in order to optimize the sensor design. A 3D model of the 8x8x0.2 mm LCP pressure sensor is simulated to investigate the parameters that significantly influence the sensor characteristics under the uniform pressure range of 0 to 50 mmHg. The simulation results of the new design are compared to the experimental results from a previous design. The result shows that reducing the thickness of the sensing membrane can increase the sensitivity up to six times of that previously reported. An improvement of fabrication methodology is proposed to complete the LCP packaging.